LEISURE ACTIVITY NEEDS AND QUALITY OF LIFE OF UPPER ELEMENTARY SCHOOL STUDENTS - Lojanasupareuk, Pornchan; Rongkhankaew, Wipongchai; Tangsujjapoj, Suvimol (Academic Journal of Thailand National Sports University, 2019)
The purposes of this survey research were to study needs of leisure activities and quality of life of upper elementary school students. Populations were 10,282 upper elementary private school students at the Office of Suratthani Elementary School Service Area in Suratthani province. 400 samples were selected by multi-stage sampling from the sample size table of Krejci and Morgan. Research instruments were: - 1) leisure activity needs questionnaire which was approved by 5 leisure experts - the range of IOC was 0.6 - 1.0, meanwhile the reliability was 0.85; and 2) the quality of life questionnaire- IOC was 0.6 -1.0, as well as the reliability was 0.90. Data were analyzed by percentage, mean and standard deviation. Findings were found that: 1) three prionrities of leisure activity that upper elementary students need most were playing music ( = 2.96), listening to music ( = 2.84) and playing badminton ( = 2.83). The highest items in each category of activities were found that, playing music ( = 2.96) in music category; listening to music ( = 2.84) in the hobby category; playing badminton ( = 2.83) in the games and sports category; and making craft ( = 2.63) in the arts and craft category. 2) Overall quality of life of upper elementary students were in the high level ( = 3.21). When considering in each category, satisfy my housing in the material category ( = 3.44) was in the highest level; then both items in having happiness and pleasure, and exciting in attend leisure activity ( = 3.42) in emotional category, receiving affection from member of family ( = 3.41) in social category, and leisure activity made me good health ( = 3.27) in physical category respectively.